Keterkaitan Harga Minyak Global dan Stabilitas IHSG Pada Pertumbuhan Ekonomi Indonesia - Febrianti Nur Khadijah; Nur Widiastuti (ISAS, 2026)
This study aims to analyze the relationship between global oil prices and the resilience of the composite stock price index (CSPI) in the context of Indonesia’s economic development. The study employs a descriptive quantitative approach, using secondary time-series data from 2019 to 2025. Global oil price data are based on the West Texas Intermediate (WTI) benchmark, while CSPI data are obtained from the Indonesian stock exchange (IDX). Data on economic growth, inflation, the rupiah exchange rate, and oil and gas exports are sourced from Statistics Indonesia (BPS) and Bank Indonesia (BI). The findings indicate that fluctuations in global oil prices influence Indonesia's economic conditions, particularly in the energy sector, inflation, the rupiah exchange rate, and the capital market. Rising global oil prices tend to increase production costs and affect investor sentiment, thereby influencing the movement of the CSPI. In addition, the CSPI has a positive relationship with economic growth as it serves as an important indicator of capital market performance and investment activity in Indonesia. During 2021–2024, increases in global oil prices were accompanied by improvements in the CSPI and in Indonesia's economic growth as the country recovered from the COVID-19 pandemic. Therefore, the stability of global oil prices and the CSPI plays a crucial role in maintaining national economic growth. Fluctuations in global oil prices affect Indonesia’s economic conditions, particularly in the energy sector, inflation, and the rupiah Keywords: global oil prices, composite stock price index (cspi), economic growth, inflation, Indonesia.